Intelligent Blockchain-Based Secure Framework for Transaction in Mobile Electronic Payment System - Adil. O. Y. Mohamed (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The rate of smartphone purchases is rising daily, and mobile payments are now frequently accepted in various areas. It is essential to transfer money completely safe as well as quick. The encrypted distributed ledgers function provides verified real-time transaction confirmation without the necessity for intermediaries like banks and clearinghouses; blockchain provide quick, secure, decentralized, and inexpensive transaction services. Blockchain technology makes money transfer simpler with transparency and financial data security. Through these capabilities, blockchain has attracted interest from around the world. However, some challenges arise while completing some financial security needs. This work proposes a framework for secure mobile payments based on blockchain technology. The advantages of blockchain are discussed and how blockchain technology provides multi-level authentication to secure mobile based financial transactions. Due to the increased safety and confidentiality of users on mobile payment apps, the suggested system takes into account the need of developing a safe application for the mobile transactions. We have also addressed the security related challenges of blockchain based payment applications and provided potential solutions.